The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/chem.200305605
|View full text |Cite
|
Sign up to set email alerts
|

Star‐Shaped Nanomolecules Based on p‐Phenylene Sulfide Asterisks with a Persulfurated Coronene Core

Abstract: Persulfurated p-phenylene sulfide (PPS) molecular asterisks (6-9) from "generations" 1 to 4 were efficiently prepared. They represent a new class of electron-accepting PPS star-shaped nanomolecules. Spectroelectrochemistry, cyclic voltammetry and UV-visible studies were performed for the asterisks and for functionalized p-phenylene sulfide oligomers (1-4). These data confirmed for the first time that an electronic delocalization through the whole asterisk molecule exists in the radical anionic or dianionic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 109 publications
1
24
1
1
Order By: Relevance
“…The UV-vis and fluorescence spectral data are comparable with those of phenylene sulfide molecular asterisk. 20,21 However, in the present study, the spectral bands are blue-shifted due to small number of phenylene sulfide linkages or groups than that in reported molecular asterisk.…”
Section: Synthesis Of Poly(phenylene Sulfide) Dendrimerscontrasting
confidence: 72%
See 1 more Smart Citation
“…The UV-vis and fluorescence spectral data are comparable with those of phenylene sulfide molecular asterisk. 20,21 However, in the present study, the spectral bands are blue-shifted due to small number of phenylene sulfide linkages or groups than that in reported molecular asterisk.…”
Section: Synthesis Of Poly(phenylene Sulfide) Dendrimerscontrasting
confidence: 72%
“…10,11 They have variety of applications from multisite catalyst, 12 multivalent glycodendrimers, 13,14 fluorescent biosensors, new conducting materials, 15 to best candidates for self assembled monolayers on gold and silver surfaces for smart materials. 16,17 Researchers have tried to synthesize the hyperbranched poly-(phenylene sulfide), 18,19 phenylene sulfide molecular asterisks 20,21 oligo(m-phenylene sulfide)s [22][23][24] and solid supported poly(thioether) dendron. 25 In present work we report the synthesis of novel poly(phenylene sulfide) dendrimers and carboxy focal poly(phenylene sulfide) dendrons by nucleophilic synthesis method and film formation of dendrimers and dendrons on mica surface.…”
mentioning
confidence: 99%
“…15 On the other hand, the catalytic transformation of thiols is significantly less developed than that of amines and alcohols, probably due to the strong thiophilicity of transition metal ions, which often lead to incompatibility of thiols with metal-catalyzed reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This is suggested by the fact that electrons are delocalized throughout the whole molecular system in the isolated DFPTC and also DPTC molecules. 7,8 We have proven the delocalization of the frontier molecular orbitals by ab initio calculations. To exemplify, the HOMO of the up-down DFPTC conformer is shown in the middle panel of Fig.…”
Section: Spectroscopic Characteristics and Electronic Functionmentioning
confidence: 99%
“…6 For instance, earlier spectroelectrochemical studies revealed a greater stabilization of the charged DPTC species, pointing to a larger delocalization of molecular orbitals, when compared to the non-substituted coronene. 7,8 These findings in combination with the non-planar molecular structure suggest that such molecules can be seen as nanosized systems with a three-dimensional delocalized electronic network.…”
Section: Introductionmentioning
confidence: 95%